2017
DOI: 10.1371/journal.pone.0177753
|View full text |Cite
|
Sign up to set email alerts
|

Fronto-temporal interactions are functionally relevant for semantic control in language processing

Abstract: Semantic cognition, i.e. processing of meaning is based on semantic representations and their controlled retrieval. Semantic control has been shown to be implemented in a network that consists of left inferior frontal (IFG), and anterior and posterior middle temporal gyri (a/pMTG). We aimed to disrupt semantic control processes with continuous theta burst stimulation (cTBS) over left IFG and pMTG and to study whether behavioral effects are moderated by induced alterations in resting-state functional connectivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…The IFG has also been a target of interest for the TBS research identified in this review. While some authors report no effects of iTBS (Anderkova et al 2018 ) nor cTBS (Wawrzyniak et al 2017 ; Anderkova et al 2018 ) to the IFG on rsFC, during task performance, the effects of both TBS protocols have been observed. Specifically, iTBS to the left IFG resulted in widespread increased network-wide activity and connectivity at frontal, occipital and cerebellar regions during phases of encoding in older adults (Vidal-Piñeiro et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The IFG has also been a target of interest for the TBS research identified in this review. While some authors report no effects of iTBS (Anderkova et al 2018 ) nor cTBS (Wawrzyniak et al 2017 ; Anderkova et al 2018 ) to the IFG on rsFC, during task performance, the effects of both TBS protocols have been observed. Specifically, iTBS to the left IFG resulted in widespread increased network-wide activity and connectivity at frontal, occipital and cerebellar regions during phases of encoding in older adults (Vidal-Piñeiro et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The IFG has also been a target of interest for the TBS research identified in this review. While some authors report no effects of iTBS (Anderkova et al, 2018) or cTBS (Anderkova et al, 2018;Wawrzyniak et al, 2017) to the IFG on rsFC, during task performance, the effects of both TBS protocols have been observed. Specifically, iTBS to the left IFG resulted in widespread increased network wide activity and connectivity at frontal, occipital and cerebellar regions during phases of encoding in older adults (Vidal-Piñeiro et al, 2014).…”
Section: Tbs To the Prefrontal Cortexmentioning
confidence: 92%
“…Similarly, functional connectivity within the visual network, acting as a control network, was not shown to be influenced by iTBS over M1 or the vertex, rather, stimulation effects remained within the stimulated motor network (Nettekoven et al, 2014). In contrast, others who have taken this approach report no significant TBS effects to either the target or control networks (Hermiller et al, 2019;Wawrzyniak et al, 2017). Hermiller et al (2019), however, reported a positive relationship between cTBS induced improvements in an offline behavioural memory task and increases in functional connectivity between the hippocampus and the target HCN, whereas a similar pattern of results was identified between the hippocampus and non-HCN regions for iTBS.…”
Section: 232mentioning
confidence: 92%
See 1 more Smart Citation
“…Collectively, the literature suggests that left anterior IFG (BA 47; pars orbitalis) and posterior IFG (BA 45; pars triangularis) mediate top-down controlled retrieval and selection of lexical representations, respectively (see Lau, Phillips, & Poeppel, 2008). Left temporal areas, found to coactivate with the frontal cortex, also play a role in control processes during meaning retrieval in addition to lexical representation/activation (e.g., Badre, Poldrack, Paré-Blagoev, Insler, & Wagner, 2005; Kuperberg, Sitnikova, & Lakshmanan, 2008; Noppeney, Phillips, & Price, 2004; Thompson-Schill, D’Esposito, Aguirre, & Farah, 1997; Wagner, Pare-Blagoev, Clark, & Poldrack, 2001; Wawrzyniak et al, 2017). Moreover, Whitney, Jefferies, and Kircher (2011) identified a functional dissociation between processes related to semantic control and representation in posterior and inferior aspects of the temporal cortex during ambiguity processing.…”
Section: Introductionmentioning
confidence: 99%